Evaluation and risk assessment of heavy metals in King tuber mushroom in the contest of COVID-19 pandemic lockdown in Sokoto state, Nigeria - Prince Onyedinma Ukaogo; Loai Aljerf; Ezeibe Chidi Nwaru; Ibrahim Imrana; Jian Tang; Atem Bethel Ajong; Precious Onyinyechi Emole; Oys Siddhant; Chizoba Thelma Ukaogo (Kuwait Journal of Science)
The aim of this study was to evaluate the degree of contamination and intake rates, as well as the risk of Lithium (Li), Arsenic (As), Cadmium (Cd), Mercury (Hg), and Lead (Pb) contained in wild species of King Tuber Mushroom (P. tuber-regium) collected pre-, post- and during the COVID-19 lockdown which is widely consumed in northwestern Nigeria; and to also assess their potential to accumulate some heavy metals, which comprises the linked consumer health hazards by assessing the risks to children, adolescents, and adults from cancer-causing and non-cancer-causing substances based on estimated weekly intake (EWI). After mineralization with acid, the concentrations were determined using Optical Emission Spectrometry with Inductively Coupled Plasma (OES-ICP), and Mercury (Hg) using Cold Vapor Atomic Fluorescence Spectrophotometer (CV-AFS). Moreover, the health risk assessment due to the ingestion of these elements through the consumption of P. tuberregium was estimated. The findings showed that concentrations of As, Pb, Cd, Li and Hg varied greatly within between 2018 and 2022, with levels higher in pre- and post- COVID-19, and lower during the COVID-19 lockdown. In descending order, the average content of these substrates and metals, was As > Pb > Cd > Li > Hg. Children, adolescents, and adults all had EWI values below the mushroom's provisional tolerable weekly intake (PTWIs). The consumption of P. tuber-regium harvested from the areas investigated, therefore, poses no toxicological or health risks to the inhabitants.